ANALISIS PELAYANAN PUBLIK DI KANTOR CABANG DINAS KEPENDUDUKAN DAN CATATAN SIPIL KECAMATAN MEHALAAN KABUPATEN MAMASA - Munawi Gay; Erlithawati Erlithawati (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2018)
This study aims to find out a number of variables that influence the public service process at the Branch Office of the Population and Civil Registry of Mehalaan District, Mamasa Regency. This type of research is quantitative by collecting data through questionnaires, interviews, observation, and documentation. Simple regression analysis is used in calculating how much influence the dependent variable has on independent. The results showed that the work performance appraisal had a significant effect on job promotion so that it could motivate employees to work harder to get a good rating. There is a relationship between Job Performance Assessment and Employee Position Promotion at the Regional Secretariat Office of Majene Regency, both of which have a significant influence.